128 Additional dietary DL-methionine affects tissue redox and inflammation status of broiler chicks in response to high stocking density. (5th December 2019) - Magnuson, Andrew; Liu, Guanchen; Sun, Tao; Tolba, Samar; Whelan, Rose; Lei, Xingen
Abstract: We determined if 30% extra supplemental DL-methionine affected oxidative and inflammatory responses of broilers stocked at a high density. A total of 560 day-old male Cornish cockerel chicks were divided into 4 groups: 2 stocking densities (2.9 and 3.8 kg/ft 2 ) and 2 methionine supplementations (grower: 2.90 or 3.77 g/kg and finisher: 2.60 or 3.38 g/kg). Chicks were fed the same corn-soy starter diet and then respective experimental diets (grower: 6.4 g SAA/kg, finisher: 5.9 g SAA/kg, n = 10 pens/treatment). Blood and tissues (3 chicks/pen) were sampled at the end of each period. Data were analyzed by two-way ANOVA. The high density elevated (P < 0.05) glutathione concentration in the plasma, breast, and thigh of growers, but decreased (P < 0.05) it in the liver of growers and thigh of finishers. The high methionine elevated (P < 0.05) glutathione concentration in the thigh at both ages. There were interactions (P < 0.05) between dietary methionine and stocking density on activities of antioxidant enzymes including GST in 2 or more tissues at both ages and GPX and SOD in the thigh of growers. Hepatic expression of inflammation-related gene IL-6 was decreased (P < 0.05) by the high density, while heat shock protein genes HSP70 and HSP90 were decreased (P < 0.05) by the high methionine. Expression of stress-related genes TNFα and JNK was decreased (P < 0.05) by a combined high methionine and density treatment. The high methionine decreased (P < 0.05) finisher thigh and breast malondialdehyde concentrations and grower plasma glucose concentrations. Neither the density nor the methionine supplementation affected concentrations of plasma ferric reducing ability, serum amyloid A, and corticosterone or hepatic protein carbonyl. In conclusion, the high stocking density showed bilateral effects on the redox and inflammatory responses of broilers. Supplemental extra methionine modulated some of those effects.